2010
DOI: 10.1093/her/cyq068
|View full text |Cite
|
Sign up to set email alerts
|

SOMOS: evaluation of an HIV prevention intervention for Latino gay men

Abstract: Latino gay men face multiple barriers to human immunodeficiency virus (HIV) prevention, in particular a lack of intervention programs that integrate prevention messages with cultural norms and address issues of social marginalization from multiple communities (gay community and Latino community), homophobia and racism. In order to address these specific issues, a multilayered HIV intervention was designed to incorporate and integrate psychosocial and community factors through multiple session groups, social ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(69 citation statements)
references
References 14 publications
1
68
0
Order By: Relevance
“…We identified four studies that examined diverse programs for the prevention and reduction of IH (Lin & Israel, 2012;Ross, Doctor, Dimito, Kuehl, & Armstrong, 2008;Vega, Spieldenner, DeLeon, Nieto, & Stroman, 2011;Yadavaia & Hayes, 2012).…”
Section: Efforts To Prevent or Reduce Ihmentioning
confidence: 99%
“…We identified four studies that examined diverse programs for the prevention and reduction of IH (Lin & Israel, 2012;Ross, Doctor, Dimito, Kuehl, & Armstrong, 2008;Vega, Spieldenner, DeLeon, Nieto, & Stroman, 2011;Yadavaia & Hayes, 2012).…”
Section: Efforts To Prevent or Reduce Ihmentioning
confidence: 99%
“…21 Although studies have included African American and Latina TW in their samples, 2,15,22,23 few have assessed contextual determinants of HIV specific to these groups. 24,25 Documentation status (legal authorization to live in the United States) is sometimes mentioned as a limitation for recruiting or retaining immigrant (noncitizen who lives in the United States) Latino/a sexual minorities in prevention and treatment, [26][27][28][29] but not as a contextual determinant of the HIV-related syndemic among transgender immigrant Latinas. For example, a prior study showed higher depressive symptoms and needs for social support among transgender Latinas compared to African Americans and Whites.…”
mentioning
confidence: 99%
“…Two (4.5%) interventions were designed to reduce sexual minority stressors and bolster coping resources and strategies simultaneously. The interventions were designed to affect change at various levels of the ecological social system, including several that simultaneously intervened at structural, interpersonal, and individual levels (e.g., Finkel et al, 2003;Vega et al, 2011). Table 1 also provides descriptive information about the methodologies used to evaluate intervention efficacy.…”
Section: Smymentioning
confidence: 99%